2010
DOI: 10.1200/jco.2009.25.7311
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen Kinetics During Follow-Up Are an Unreliable Trigger for Intervention in a Prostate Cancer Surveillance Program

Abstract: Postdiagnostic PSA kinetics do not reliably predict adverse pathology and should not be used to replace annual surveillance biopsy for monitoring men on active surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(175 citation statements)
references
References 15 publications
5
161
1
8
Order By: Relevance
“…Although men from this cohort already selected for treatment were not included in this analysis, it does suggest that PSA kinetics are not static, and single PSA trigger points should be interpreted carefully. Further questioning the role of PSA changes over time for men on AS, the Johns Hopkins group showed no correlation between PSA DT and adverse pathology at surveillance biopsy or RP for those who eventually underwent surgical management [42]. Similarly, within the UCSF cohort, little concordance was found between PSAV and biopsy progression [43].…”
Section: 5mentioning
confidence: 99%
“…Although men from this cohort already selected for treatment were not included in this analysis, it does suggest that PSA kinetics are not static, and single PSA trigger points should be interpreted carefully. Further questioning the role of PSA changes over time for men on AS, the Johns Hopkins group showed no correlation between PSA DT and adverse pathology at surveillance biopsy or RP for those who eventually underwent surgical management [42]. Similarly, within the UCSF cohort, little concordance was found between PSAV and biopsy progression [43].…”
Section: 5mentioning
confidence: 99%
“…For example, Ross et al analyzed the association between PSA kinetics and biopsy progression in a group of 290 men managed with AS at their institution. 5 Over a median follow-up period of 2.9 years, 35% of these men developed biopsy progression. The authors were not able to find any PSAV or PSADT cut-points with both high sensitivity and specificity for biopsy progression.…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for AS are likely to have a large prostate as a result of inclusion criteria regarding PSA density, and anterior tumors are often missed. 4 Furthermore, rebiopsy is associated with complications and mental distress, 5 and is thus a serious problem for both patients and physicians alike. 1 More reliable and less invasive methods are required for favorable outcomes after AS.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Toronto cohort, 100% of patients who have progressed to metastatic disease have had a PSA doubling time < 2 years. However, some recent studies have questioned the correlation between PSA kinetics and adverse disease characteristics [25]. A recent overview of this subject concluded that PSA kinetics, although predictive, did not add predictive value to absolute PSA, and should not be used for decision making in localized prostate cancer [26].…”
Section: Triggers For Interventionmentioning
confidence: 99%